ANALISIS KOMUNIKASI DATA PADA ALAT MONITORING PASIEN RUMAH SAKIT MENGGUNAKAN MODUL LORA 923 MHz - Mochammad Mufti Nurmukhlis; Ponco Siwindarto; Rusmi Ambarwati (Jurnal Mahasiswa TEUB, 2023)
LoRa is one of the most popular LPWAN technologies. LoRa technology is suitable for IoT application scenarios that only need to transmit small amounts of data over long distances and transmit data at low power. The tool system for monitoring hospital patients aims to help and speed up medical records of health services, both under normal circumstances and in critical or urgent situations. LoRa functions as a long-range spectrum communication medium to receive data sent from the detector subsistence. This research focuses on testing Heltec's LoRa range at 923MHz frequency. The parameters used are Received Signal Strength Indicator (RSSI) and Packet loss. The RSSI test results will be compared with the RSSI calculated using the normal log shadowing model. Calculations for the free space area with the addition of shadowing effects. Judging from the range of RSSI values at each test point, RSSI is relatively stable. However, based on the average RSSI testing and calculations, RSSI has decreased while packet 2 loss has increased with each additional distance. From this study, the maximum LoRa range is 180 meters. Keywords: LoRa, IoT, RSSI